The Effect of CM082, an Oral Tyrosine Kinase Inhibitor, on Experimental Choroidal Neovascularization in Rats. (22nd October 2017) - Ren, Chengda; Shi, Hui; Jiang, Juanjuan; Liu, Qingyu; Du, Yaru; He, Mengmei; Cai, Wenting; Wei, Qingquan; Yu, Jing
Abstract : The aims of this study were to evaluate the effects of CM082 on the development of choroidal neovascularization (CNV) in a laser-induced CNV rat model and to determine the drug concentration in the ocular tissues. After the laser-induced CNV model was established in rats, CM082 was orally administered. The effects of CM082 on the CNV lesions were assessed using fundus fluorescein angiography (FFA), CNV histology, and retinal pigment epithelium- (RPE-) choroid-sclera eyecup analysis. The concentrations of CM082 in the plasma and eye tissues were determined using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results of FFA, histology, and RPE-choroid-sclera eyecup analysis demonstrated that the CM082-treated (10 mg/kg/d or 30 mg/kg/d) rats exhibited significantly less neovascularization than did the control group. The total concentration of CM082 in the eyes (172.86 ± 57.11 ng/g) was similar to that in the plasma (196.87 ± 73.13 ng/ml). Within the eye, the concentrations of CM082 and its metabolites were highest in the retina-sclera. The orally administered CM082 thus effectively passed through the blood-retina barrier (BRB) to reach the retina in the Brown Norway rats. Therefore, at both 10 mg/kg/d and 30 mg/kg/d, CM082 was able to reduce CNV lesions in the laser-induced CNV rat model.